2021
DOI: 10.1021/acsami.1c04525
|View full text |Cite
|
Sign up to set email alerts
|

Stability-Enhanced α-Ni(OH)2 Pillared by Metaborate Anions for Pseudocapacitors

Abstract: α-Ni­(OH)2 is an ideal candidate material for a supercapacitor except for its low conductivity and poor stability. In this work, BO2 –-intercalated α-Ni x Co(1–x)(OH)2 is synthesized by a hydrothermal method at a low cost. The Co dopant can decrease the charge-transfer resistance and enhance the cyclic stability. The special unsaturated electronic state of BO2 – enhances the bonding with metal ions and attracts water molecules. Thus, the BO2 – ions support the hydroxide layers as pillars and create efficient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…It is reported that the existence of Co 3+ improves the conductivity of Ni-Co hydroxides. 10 Thus, the strong correlation between Co contents and conductivity could be attributed to the higher concentration of Co 3+ in the Co abundant Ni-Co-LDH-Cs, which has been confirmed by XPS results.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…It is reported that the existence of Co 3+ improves the conductivity of Ni-Co hydroxides. 10 Thus, the strong correlation between Co contents and conductivity could be attributed to the higher concentration of Co 3+ in the Co abundant Ni-Co-LDH-Cs, which has been confirmed by XPS results.…”
Section: Resultssupporting
confidence: 57%
“…3c), where the corresponding characteristic peaks located at 1324, 1420 and 1577 cm À1 typically are assigned to varied n(-COO-) modes and that at 1074 cm À1 is assigned to the n(C-O) modes. Based on the structure and previous reports, 10,25 it is reasonable to assume that citrate acts as charge balancing anions and pillars in the interlayer to stabilize the a-phase layer structure with a wide interlayer spacing, which is critically important for improving the capacity retention of Ni-Co-LDH-Cs during the charge-discharge process. The survey XPS spectra (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In recent years, transition-metal hydroxide, especially Ni(OH) 2 , has attracted intensive concerns as a result of its low cost, remarkable energy density and theoretical specific capacitance [14][15][16]. Even so, the shortcomings of inferior electric conductivity and poor rate capability are becoming serious obstacles to the widespread application of supercapacitors [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%